2011
DOI: 10.1007/978-3-642-22878-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Diffusion of Theories, Models, and Theoretical Constructs in eGovernment Research

Abstract: Abstract. After more than a decade of research in the field of e-government, it is now timely and appropriate to reflect upon the overall developmental directions in the area. The purpose of this paper is to explore research progress to date by systematically analysing the existing body of knowledge on egovernment related issues. Usable data relating to e-government research currently available were collected from 434 research articles. Based on the investigation of the various studies, our findings reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…However, the mere presence of e-government offers does not suffice to induce positive effects among citizens (Morgeson & Petrescu, 2011). Sophisticated attitudinal multivariate studies, which address success factors of e-government usage, mainly focus on established models of information system research to explain citizens' e-government usage behavior (Rana, Williams, Dwivedi, & Williams, 2011). Theoretical approaches and empirical scales of information system research, for example the DeLone & McLean IS success model (DeLone & McLean, 1992;DeLone & McLean, 2003), and of electronic commerce, for example SERVQUAL, are often structurally adapted to specific e-government services like tax-filing systems in this regard Chen, 2010;Floropoulos, Spathis, Halvatzis, & Tsipouridou, 2010;Hu et al, 2009).…”
Section: Status Quo Of E-government Research and Research Proceedingsmentioning
confidence: 99%
“…However, the mere presence of e-government offers does not suffice to induce positive effects among citizens (Morgeson & Petrescu, 2011). Sophisticated attitudinal multivariate studies, which address success factors of e-government usage, mainly focus on established models of information system research to explain citizens' e-government usage behavior (Rana, Williams, Dwivedi, & Williams, 2011). Theoretical approaches and empirical scales of information system research, for example the DeLone & McLean IS success model (DeLone & McLean, 1992;DeLone & McLean, 2003), and of electronic commerce, for example SERVQUAL, are often structurally adapted to specific e-government services like tax-filing systems in this regard Chen, 2010;Floropoulos, Spathis, Halvatzis, & Tsipouridou, 2010;Hu et al, 2009).…”
Section: Status Quo Of E-government Research and Research Proceedingsmentioning
confidence: 99%
“…Facilitating condition is the perception of individuals about the resources and support that is given by the environment in shaping up particular behaviour (Rana, Williams, Dwivedi, & Williams, 2011). In the context of e-government service adoption, facilitating conditions are the grade to which citizen perceives that sufficient resources provided by the government which assists and facilitates them in using e-services provided by the government.…”
Section: Facilitating Conditionmentioning
confidence: 99%
“…Various meta-analyses concluded that for e-government development various variables might be relevant that can be grouped similarly to the model used in the paper. For instance, Rana et al (2011) enumerate the following groups of variables that can be used in researching e-government: environmental characteristics, organizational characteristics, individual characteristics and innovation characteristics. Chen (2010) diff erentiates environmental setting, institutional characteristics, government capacity and government style.…”
Section: Theoretical Background and Methodologymentioning
confidence: 99%